The Pelanggaran Etika Guru Dan Dampaknya Terhadap Karakter Siswa: Kajian Literatur - Arfan Amrullah; Khumaidatun Nisa; Abdul Hafid Al Haq; Abul Mafaakhir (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study aims to analyze the concept of professional ethics for teachers, identify forms of ethical violations, and examine their impact on student character development. The method used is a qualitative approach involving library research through the collection of secondary data from books, scientific journals, and relevant previous studies, which were then analyzed using content analysis. The results of the study indicate that violations of teacher ethics still occur in various forms, such as unfair treatment of students, professional indiscipline, abuse of authority, and violations in the use of digital media. These violations have a significant impact on student character, including decreased motivation to learn, the development of negative behavior, a loss of respect for teachers, and disruption of students’ psychological well-being. This study contributes to strengthening the understanding that teacher ethics is the primary foundation for the success of character education, while also emphasizing the importance of the teacher’s role as a role model. However, this study has limitations as it is based solely on a literature review without empirical field data. empirical approach is recommended to corroborate these findings, along with the need to strengthen the implementation of the code of ethics, enhance teacher competence, and establish a more effective monitoring system to prevent ethical violations in the educational setting.